Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Merek Vans di Jakarta - Kevin; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine how much influence brand image and product quality had on the decision to purchase Vans brand shoes in Jakarta. This study discusses the dimensions of the research variables and to determine the influence between variables and objects. The study used a quantitative method obtained using SPSS version 20 through a questionnaire distributed to 150 respondents using the non-probability sampling method. The results of hypothesis testing indicate that the brand image variable has a significant effect on purchasing decisions. Product quality variable has a significant effect on purchasing decisions . This research was conducted to provide an understanding for the Vans company to pay attention and continue to improve brand image and product quality.